2012
DOI: 10.1371/journal.pone.0034788
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Improves Growth Retardation Induced by Rapamycin without Blocking Its Antiproliferative and Antiangiogenic Effects on Rat Growth Plate

Abstract: Rapamycin, an immunosuppressant agent used in renal transplantation with antitumoral properties, has been reported to impair longitudinal growth in young individuals. As growth hormone (GH) can be used to treat growth retardation in transplanted children, we aimed this study to find out the effect of GH therapy in a model of young rat with growth retardation induced by rapamycin administration. Three groups of 4-week-old rats treated with vehicle (C), daily injections of rapamycin alone (RAPA) or in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Since LiCl is able to activate the PI3K/-Akt pathway and to inhibit GSK3β [ 30 , 35 ], it can be considered as a mimicker of insulin or other growth factors or inflammatory cytokines that lead to GSK3β inactivation as a result of PKC/PI3K/Akt activation [ 36 , 37 ], whereas the comparison with SB216763 and GSK3β silencing strategies can help in distinguishing the effects which are uniquely dependent on GSK3β inactivation versus those which are instead dependent on other signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Since LiCl is able to activate the PI3K/-Akt pathway and to inhibit GSK3β [ 30 , 35 ], it can be considered as a mimicker of insulin or other growth factors or inflammatory cytokines that lead to GSK3β inactivation as a result of PKC/PI3K/Akt activation [ 36 , 37 ], whereas the comparison with SB216763 and GSK3β silencing strategies can help in distinguishing the effects which are uniquely dependent on GSK3β inactivation versus those which are instead dependent on other signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike what we observed in Rpt +/-mice, we found that rapamycin administration inhibited bone growth in control mice, suggesting that the systemic administration of rapamycin may have altered additional pathways that are converging on bone growth, consistent with previously published results (Supplemental Figure 6, A and B and ref. 32).…”
Section: Gfp-lc3mentioning
confidence: 99%
“…Additionally, mTOR signaling can also regulate other cells which play role in skeletogenesis. Reportedly, rapamycin reduces the proliferation of chondrocytes, endotheliocytes, and periosteum cells, destroy mature and hypertrophic chondrocytes, and inhibits vasculogenesis of chondrocytes (Alvarez‐Garcia et al, 2010; Álvarez‐García et al, , ; Holstein et al, ; Sanchez & He, ). Interestingly, bafilomycin A1 and chloroquine (both are inhibitors of autophagy) are found to activate mTORC1 signaling in autophagy‐independent manner unexpectedly, which is observed exclusively in chondrocytes but not in osteoblasts, fibroblasts, or liver cells (Newton, Vuppalapati, Bouderlique, & Chagin, ).…”
Section: Implications Of Mtor Signaling In Osteoporosismentioning
confidence: 99%
“…On the basis of previous numerous types of clinical evidences (Bruyn et al, 2008;Lai et al, 2012;Su et al, 2009) Several basic studies reveal that rapamycin can suppress the growth of body weight, alter the normal structure and dynamic equilibrium of growth plate, retard the growth of long bone, and influence fracture healing of femur (Álvarez-García et al, 2007(Álvarez-García et al, , 2010(Álvarez-García et al, , 2012Holstein et al, 2008;Phornphutkul et al, 2009;Sanchez & He, 2009;Yang et al, 2015). Recently, anticancer synergy with the use of mTOR signaling inhibitors have been postulated in osteosarcoma treatment, suggesting that mTOR inhibition may also have a positive impact on bone (Moriceau et al, 2010).…”
Section: Implications Of Mtor Signaling In Osteoporosismentioning
confidence: 99%